Cuidados de enfermagem para o paciente pediátrico com dermatite atópica ou epidermólise bolhosa: revisão integrativa - Moura, Matheus Henrique Alves De (2022)
Atopic Dermatitis and Epidermolysis Bullosa are chronic diseases that affect the morphological and biochemical structure of the skin, leading to lesions and systemic changes in affected individuals, which can cause generalized infections. They are commonly diagnosed in early childhood, and the nurse can intervene early to help the child during the physical, psychological and social development process. This study aimed to conduct an integrative literature review to identify the best available evidence on nursing care and the clinical and symptomatic management of these conditions in pediatric patients during infancy and early childhood. For this, the guiding question was “What is the nursing care for pediatric patients with atopic dermatitis or epidermolysis bullosa?”. The following databases were used: Medical Literature Analysis and Retrieval System Online (Medline) via PubMed, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Latin American Literature in Health Sciences (LILACS) and Health Care Ibero-America (CUIDEN). The founded duplicates, were excluded on the ENDnote software. Two independent reviewers selected the studies that answered the guiding question using the Rayyan software, by reading the title and abstract. After that, the studies were fully read, reaching the final sample of 23 studies that answered the guiding question. Data were extracted and presented through two major categories: Nursing Care for Children with AD and EB and Health Education. The study contributed to the discussion of what are the best nursing actions in the clinical and symptomatological management of diseases, as well as it was able to highlight the potential and difficulties of the professionals in assisting people affected by the conditions. There is still a lack of publications about epidermolysis bullosa, and it can be justified by the fact that it is a rare condition and requires specific treatment.